[Cu2(en)2(N3)4]n – A new member in the family of copper(II)-azido assemblies: structural and magnetic studies. Issue 7 (3rd April 2017) - Pandey, Priyanka; Kharediya, Bhagwan; Elrez, Bahjat; Sutter, Jean-Pascal; Sunkari, Sailaja S.
Abstract: A copper(II) complex with ethylene diamine and azide, viz., [Cu2 (en)2 (N3 )4 ]n has been isolated under self-assembling conditions and characterized both structurally and magnetically in order to probe the role of reactant molar ratios in generating supramolecular assemblies with strong magnetic interactions toward achieving molecule-based magnets as a long-term objective. The title structure with ferromagnetic interactions is an intermediate member in the family of copper-azido assemblies involving ethylene diamine, obtained by systematic modifications in the reactant molar ratios, highlighting the inherent difficulty in controlling the final solid formation and potential of the delicate equilibrium conditions in directing supramolecular structures, which may display interesting structure-correlated properties. The structure is a chain of μ -1, 1 bridged dimers of Cu2, connected to Cu1 through μ -1, 3 azide bridges, leading to a rail-road arrangement of polymeric chains. Two such parallel chains are further linked to each other through Cu3, which is connected to Cu2′ of the dimer, through asymmetric end-on μ -1, 1 azide bridges, resulting in a 2-D network in the unit cell. The magnetic behavior revealed ferromagnetic interactions in Cu(II) pairs and is dominated by overall antiferromagnetic interactions within the network. Abstract :